The Relationship Between Parents' Parenting Patterns And Addiction To Playing Online Games In Youth In Rantau Ketaka Village Lunang District, Pesisir Selatan Regency - Vera Jumaini; Syur’aini Syur’aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The rapid development of technology has caused several impacts, both positive and negative. This is the background of this research, namely the high level of addiction to playing online games among teenagers and the low parenting style of parents in Rantau Ketaka, Kecamatan Lunang, Kabupaten Pesisir Selatan. This study aims to see whether there is a relationship between arenting patterns and addiction to playing online games in adolescents.The research method used is correlational quantitative. In this study, the data sources were teenagers in Rantau Ketaka Village, Lunang District, Pesisir Selatan Regency, amounting to 33 people. The sample in this study amounted to 25 adolescents using purposive random sampling technique. The type of data in this study is data about the form of parenting and the level of addiction to playing online games in adolescents in Rantau Ketaka Village, Kecamatan Lunang, Kabupaten Pesisir Selatan. This study uses a questionnaire for data collection by using data analysis techniques percentage and rank spearmen.The results showed that there was a significant relationship between parenting and addiction to playing online games in adolescents in Rantau Ketaka Village, Lunang District, Pesisir Selatan Regency. Suggestions in this research are highly expected. It is hoped that parents in Rantau Ketaka Village can apply appropriate parenting to their children to avoid addicted behavior playing online games in teenagers.Keywords: parenting, addiction, online games